(449) مقدمة في دراسة الإنتاجية على المستوى القومى Introduction to the Study of Productivity at the National Level - مدحت محمد العقاد (معهد التخطيط القومي, 2026)
ل هذه المذكرة الأهمية الاستراتيجية لـ "الإنتاجية" كمؤشر أساسي لكفاءة استغلال الموارد وتأثيرها المباشر على التنمية الاقتصادية ومستويات المعيشة، يستعرض البحث تعريف الإنتاجية كعلاقة قابلة للقياس بين الناتج والموارد المستخدمة (عمل، رأس مال، مواد خام)، مفرقاً بين قياس الإنتاجية على مستوى الاقتصاد القومي وبين قياسها القطاعي (زراعة، صناعة، خدمات). كما يناقش البحث الجدل حول المفاضلة بين الأساليب الإنتاجية "كثيفة رأس المال" و"كثيفة العمل"، مبيناً أثر كل منهما على معدلات النمو والتوظيف في الأجلين القصير والطويل ، وتسلط الضوء أيضاً على العوامل المؤثرة في نمو الإنتاجية، مقسماً إياها إلى عوامل عرض وسائل الإنتاج (كالمدخرات والتقدم الفني) وعوامل الطلب المحلي والخارجي، ويقدم البحث مقارنة دولية تظهر الفجوة الواسعة في مستويات الإنتاجية بين الدول المتقدمة والنامية، مرجعاً هذه الاختلافات إلى تفاوت مستويات التعليم، ومقدار رأس المال المتاح لكل عامل، والكفاءة التنظيمية والتكنولوجية ، ويختتم البحث بالتأكيد على أن زيادة الإنتاجية هي السبيل الوحيد لرفع رفاهية المجتمع وتحقيق قفزات تنموية حقيقية تتجاوز الاختلالات الهيكلية في الاقتصاد . This memorandum highlights the strategic importance of "productivity" as a key indicator of resource utilization efficiency and its direct impact on economic development and living standards. The research reviews the definition of productivity as a measurable relationship between output and the resources used (labor, capital, raw materials), differentiating between measuring productivity at the national economic level and measuring it at the sectoral level (agriculture, industry, services). The research also discusses the debate surrounding the trade-off between "capital-intensive" and "labor-intensive" production methods, demonstrating the impact of each on growth and employment rates in the short and long term. It also sheds light on the factors affecting productivity growth, dividing them into factors of the supply of means of production (such as savings and technological progress) and factors of domestic and external demand. The research presents an international comparison that reveals the wide gap in productivity levels between developed and developing countries, attributing these differences to varying levels of education, the amount of capital available per worker, and organizational and technological efficiency. The research concludes by emphasizing that increasing productivity is the only way to raise societal well-being and achieve genuine developmental leaps that overcome structural imbalances in the economy.